Results in mechanical properties and wear behaviour of AA6061-Si3N4 composites - J. Kumaraswamy; L. Bharath; K.C. Anil; T.M. Geetha; R. Nagesh (Results in Surfaces and Interfaces)
The wear attributes of in-situ stir cast AA 6061-Si3N4 nanocomposites were examined in this study. The composites were made using varied Si3N4 concentrations (3.0, 6.0, 9.0, and 12.0 wt%) in a metal salt reaction. Optical microscopy and Energy Dispersive X-ray Spectrometry (EDS) were both used to analyse the microstructure of the composite materials. The homogeneous distribution of Si3N4 particles in the AA 6061 matrix was clearly visible in the microstructures. A dry sliding wear test was conducted using a pin-on-disk tester under various time, load, sliding distance, and speed conditions. The composite materials shown better wear resistance than the AA 6061 matrix. Additionally, the wear rate decreased as Si3N4 content increased for all applied loads, sliding distances, and velocities. Due to the incorporation of tiny silicon nitride particles into the matrix and the strong interfacial connection between the in-situ reinforcement and the matrix alloy, the composites showed decreased wear rates. It was revealed that the wear rate of Si3N4 reinforced composites was comparable to that of automotive industry-used cast iron brake drums. According to SEM images, abrasive wear at lower stresses and adhesive wear at higher loads mostly helped in material removal.